Dually Stabilized Triblock Copolymer Micelles with Hydrophilic Shell and Hydrophobic Interlayer for Systemic Antisense Oligonucleotide Delivery to Solid Tumor - Kim, Beob Soo; Kim, Hyun Jin; Osawa, Shigehito; Hayashi, Kotaro; Toh, Kazuko; Naito, Mitsuru; Min, Hyun Su; Yi, Yu; Kwon, Ick Chan; Kataoka, Kazunori; Miyata, Kanjiro (American Chemical Society, 2019)
For intravenous delivery of antisense oligonucleotides (ASOs) to solid tumors, a triblock copolymer was synthesized from poly(2-ethyl-2-oxazoline) (PEtOx), poly(2-n-propy1-2-oxazoline) (PnPrOx), and poly(L-lysine) (PLL) segments. The triblock copolymer, PEtOx-PnPrOx-PLL, was utilized to fabricate a compartmentalized polymeric micelle featuring a hydrophilic PEtOx shell, thermoresponsive PnPrOx interlayer, and ASO/PLL polyion complex (PIC) core. In this formulation, the PnPrOx-derived interlayer underwent the phase transition from hydrophilic elongated state to hydrophobic collapsed state at a lower critical solution temperature (LCST) to enhance the micelle stability. Three triblock copolymers comprising varying lengths of PEtOx segment (2k, 7k, and 12 kDa) were compared to investigate the effect of hydrophilic chain length on the micelle properties. The triblock copolymer micelles (TCMs) were prepared in a two-step manner: mixing between triblock copolymer and ASO in a buffer solution at 4 degrees C and then increasing the temperature of the solution up to 37 degrees C. This protocol was crucial for the fabrication of TCMs with both smaller size and narrower size distribution, probably due to the formation of the well-compartmentalized hydrophobic interlayer in the micelle structure. The presence of the PnPrOx segment dramatically enhanced the stability of TCMs in serum-containing media and elicited more efficient cellular uptake of ASO payloads, resulting in higher gene silencing efficiency in cultured prostate cancer (PC-3) cells, compared with a control diblock copolymer micelle (DCM). The blood circulation property of TCMs was prolonged with an increase in the length of PEtOx segment, permitting the efficient accumulation of ASO payloads in a subcutaneous PC-3 tumor model. Ultimately, the systemic delivery of ASO targeting a long noncoding RNA (lncRNA) by the TCMs significantly reduced the expression level of lncRNA in the subcutaneous PC-3 tumor in a sequence-specific manner. These results demonstrate the superiority of TCMs equipped with the hydrophilic shell and hydrophobic interlayer to the cancer-targeted systemic ASO delivery.